Gender and Age Aspects within the Pragmatic Potential of the Epistemic Modality Markers - Shakirova, Rezeda D.; Safina, Adelina R. (Journal of History Culture and Art Research, 2019)
It is well known that the representatives of a certain gender and age groups are distinguished by various perceptions of the world, evaluation of the objective reality events as well as by operating facts as reliable. The purpose of the research is to reveal the speaker’s gender and age characteristics affecting the confidence level in reliability of facts provided and as such the epistemic modal markers (modal words and modal verbs) chosen by him or her. To achieve the objective of the research there were used some linguistic methods such as a communicative-pragmatic and the descriptive ones. The illustrative basis consists of the situations expressing the meanings of epistemic possibility and epistemic necessity. Two types of literary characters from two fiction resources (J. Banville «The Sea» and M. Zusak «The Book Thief») were chosen to analyse: a middle-aged man and a teenage girl. The research identifies that the man mostly deals with markers of epistemic possibility if his statement is based on retrospection, intuition, or faith / conjecture (unlike a girl), an assumption (similar to a girl). In case of having a convincing evidence base, the man uses epistemic necessity markers. The girl demonstrates the usage of modal markers of epistemic necessity if her statements are based on faith, desire to benefit or “female logic”. The desire to attract attention of the opposite sex interlocutor is marked by the usage of modal markers of epistemic possibility. It is also worth noting that strong emotions, which are common to a teenage girl rather than a mature man, can distort the reliability of the statements. The content of the article is of practical value for the further epistemic modality researches in the field of linguistic pragmatics and sociolinguistics.